Analisis Tindak Pidana Korupsi Dalam Pengelolaan BUMN PT Pertamina - Sulaeman, Fauzia Putri (Bandung Conference Series: Law Studies, 2022)
Abstract. The background of the research here is about the corruption case that occurred in a subsidiary of BUMN, especially PT Pertamina, which was carried out by the Board of Directors of PT Pertamina, namely Karen Agustiawan. The case here has ensnared Karen with Article 2 of the Corruption Act. After going through the cassation period, Karen was released from her demands. This research aims to find out and explain the formulation of the problem regarding the consideration of the cassation judge against the perpetrators of criminal acts of corruption in the case of a BUMN subsidiary, especially PT Pertamina's positive law in Indonesia. And the interpretation of the judge's decision and its best considerations in acquitting the Defendant in Decision Number 121 K/Pid.Sus/2020. The method in this research used a normative juridical method, with a qualitative approach. The results of this research here are the consideration of the cassation judge who saw that the corruption that occurred in the case here was an actual loss of business and caused a misunderstanding for the public prosecutor about his decision. Therefore, the Supreme Court judge acquitted Defendant Karen against all of her claims because it has been stated in PERMA Number 10 of 2020 concerned that the subordinates of BUMN companies are not subject to BUMN, so what happens is only business losses. Abstrak. Penelitian disini melatarbelakangi tentang kasus korupsi yang terjadi dalam anak perusahaan BUMN khususnya PT Pertamina, yang dilakukan oleh Direksi PT Pertamina yaitu Karen Agustiawan. Yang mana kasus disini telah menjerat Karen dengan Pasal 2 Undang-Undang Tindak Pidana Korupsi. Setelah melewati masa kasasi akhirnya Karen telah di lepas bebas dari segala tuntutannya. Penelitian disini bertujuan agar dapat mengetahui dan menjelaskan rumusan masalah tentang pertimbangan hakim kasasi terhadap pelaku tindak pidana korupsi dalam kasus anak perusahaan BUMN khususnya PT Pertamina menurut hukum positif di Indonesia. Dan penafsiran putusan hakim dan pertimbangan terbaiknya dalam membebaskan Terdakwa pada Putusan Nomor 121 K/Pid.Sus/2020. Metode dalam melakukan penelitian disini mengunakan metode yuridis normatif, dengan pendekatan kualitatif. Hasil pada penelitian disini yaitu pertimbangan hakim kasasi yang dilihat pada korupsi yang terjadi dalam kasus disini merupakan rill dari kerugian bisnis dan menjadikan kesalah pahaman bagi JPU terhadap putusannya. Maka dari itu hakim MA membebaskan Terdakwa Karen terhadap segala tuntutannya, dikarenakan telah di sebutkan dalam PERMA Nomor 10 Tahun 2020 tentang anak buah perusahaan BUMN tidak tunduk kepada BUMN maka yang terjadi hanyalah kerugian bisnis.